Plasmonic Backscattering Effect in High‐Efficient Organic Photovoltaic Devices. Issue 2 (16th November 2015) - Kakavelakis, George; Vangelidis, Ioannis; Heuer‐Jungemann, Amelie; Kanaras, Antonios G.; Lidorikis, Elefterios; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : A universal strategy for efficient light trapping through the incorporation of gold nanorods on the electron transport layer (rear) of organic photovoltaic devices is demonstrated. Utilizing the photons that are transmitted through the active layer of a bulk heterojunction photovoltaic device and would otherwise be lost, a significant enhancement in power conversion efficiency (PCE) of poly[N‐9′‐heptadecanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)]:phenyl‐C71 ‐butyric acid methyl ester (PCDTBT:PC71 BM) and poly[[4, 8‐bis[(2‐ethylhexyl)oxy]benzo[1, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diyl][3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3, 4‐b] thiophenediyl]] (PTB7):PC71 BM by ≈13% and ≈8%, respectively. PCEs over 8% are reported for devices based on the PTB7:PC71 BM blend. A comprehensive optical and electrical characterization of our devices to clarify the influence of gold nanorods on exciton generation, dissociation, charge recombination, and transport inside the thin film devices is performed. By correlating the experimental data with detailed numerical simulations, the near‐field and far‐field scattering effects are separated of gold nanorods (Au NRs), and confidently attribute part of the performance enhancement to the enhanced absorption caused by backscattering. While, a secondary contribution from the Au NRs that partially protrude inside the active layer and exhibit strong near‐fields due to localized surface plasmon resonance effects is also observed but is minor in magnitude. Furthermore, another important contribution to the enhanced performance is electrical in nature and comes from the increased charge collection probability. Abstract : High efficiency organic photovoltaic (OPV) devices are fabricated based a novel and universal light trapping mechanism, using gold nanorods (Au NRs) as back contact reflectors. The incorporation of Au NRs inside the back contact interfacial layer (titanium sub oxide) gives rise to a device efficiency of ≈13%, compared to the record performance of 8.25%. This is revealed to be mainly due to scattering by a combination of theoretical and experimental results.